A first-principles study on the effect of Cr, Mn, and Co substitution on Fe-based normal- and inverse-Heusler compounds: Fe3−xYxZ (x=0, 1, 2, 3; Y= Cr, Mn, Co; Z=Al, Ga, Si) - Huang, Hung-Lung; Tung, Jen-Chuan; Jeng, Horng-Tay (Frontiers in Physics, 2022)
First-principles calculation has become one of the most reliable approaches in predicting struc- tural, electronic, and magnetic properties for material applications. Alloys in Heusler structures have also attracted much attention recently since they can be easily synthesized and provide inter- esting properties for future spintronic applications. In this work, we investigate a series of Fe-based Heusler compounds Fe3−x Yx Z (x=0, 1, 2, 3; Y= Cr, Mn, Co; Z= Al, Ga, Si) with L21 - and XA- type structures using first-principles calculations based on density functional theory. According to formation energy calculations and mechanical property analysis, most of the studied Heusler compounds are thermodynamically stable and could be synthesized experimentally. The Co sub- stitution leads Fe3−x Cox Z to a ferromagnetic ground state like Fe3 Z with a strong magnetization ranging from 4 to 6 μB /f.u. While replacing Fe with Cr or Mn, the exchange coupling between Cr (Mn) and its neighboring atoms generally tend to be anti-parallel. Among the antiferromagnetic compounds, Mn3 Al and Mn3 Ga are antiferromagnetic half metal while Mn3 Si is ferrimagnetic half metal. These rarely found type of half metals with low magnetic moment and high spin polarization at the Fermi level are important for low energy consumption spintronic applications. The estimated Curie temperatures for Mn3 Al, Mn3 Si and Co2 FeSi (XA) are in good agreement with previously theoretical values, while for Fe3 Al and Fe3 Si, they are in good agreement with previous experimental results. The good consistency in Curie temperature demonstrates high reliability of our predictions based on first-principles calculations. As for the topological property aspect, we predict Fe2 CrAl and Fe2 MnAl as the 3-dimensional Weyl semimetal. Furthermore, Fe2 CrSi is predicted to be the magnetic nodal-line semimetal. Interestingly, our mechanical property analysis demonstrates that Co3 Si and Fe2 CoSi (L21 ) exhibit ultraelastic metal behavior, which is of high potential in advanced mechanical industry. This work suggests that Heusler compounds are excellent candidates for future spintronics as well as for high-performance ultraelastic metals.